2003
DOI: 10.1002/app.11741
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of ultrasonically devulcanized unfilled SBR, NR, and EPDM rubbers

Abstract: ABSTRACT:The comparative study of the continuous ultrasonic devulcanization of various unfilled rubbers [natural rubber, styrene-butadiene rubber (SBR), ethylene-propylene-diene rubber (EPDM)] is carried out by means of a ultrasonic reactor. The power consumption, gel fraction, crosslink density, cure behavior, and physical properties of devulcanized rubbers were measured. The glass transition temperatures of virgin, vulcanized, and devulcanized rubbers were determined in order to characterize the difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
2
18
1
Order By: Relevance
“…Figure 3 shows the ultrasonic power consumption and pressure at the entrance to the devulcanization zone during the devulcanization of butyl rubber at a flow rate of 1 g/s, a gap of 0.5 mm, and a die exit opening of 29.2 mm. As observed for other rubbers,14, 26 the power consumption increased with the increase in the ultrasonic amplitude, and the die pressure decreased with the increase in the ultrasonic amplitude. This was explained as the combined effect of the softening of rubber due to devulcanization, the reduction in friction between rubber particles and the horn surface, and an increasing material temperature at the treatment zone due to ultrasonic vibration 13…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Figure 3 shows the ultrasonic power consumption and pressure at the entrance to the devulcanization zone during the devulcanization of butyl rubber at a flow rate of 1 g/s, a gap of 0.5 mm, and a die exit opening of 29.2 mm. As observed for other rubbers,14, 26 the power consumption increased with the increase in the ultrasonic amplitude, and the die pressure decreased with the increase in the ultrasonic amplitude. This was explained as the combined effect of the softening of rubber due to devulcanization, the reduction in friction between rubber particles and the horn surface, and an increasing material temperature at the treatment zone due to ultrasonic vibration 13…”
Section: Resultssupporting
confidence: 71%
“…The virgin vulcanizate and revulcanized samples had higher T g 's than the corresponding virgin gum and devulcanized samples. Clearly, the glass‐transition temperatures of butyl rubber increased upon crosslinking because of the reduced mobility of the chains, as typically observed for other rubbers 26…”
Section: Resultsmentioning
confidence: 53%
“…Table 3 shows 4 Gel fraction of devulcanised NR as function of cycles of mechanochemical milling 14 who reported that after the NR vulcanisate has been devulcanised through ultrasonic devulcanisation process, an increase of 4uC in T g value could be observed. They ascribed the increase to the transformation of polysulfidic cross-links into cyclic sulphidic structures chemically linked to the backbone chain during ultrasonic treatment, which leads to the decrease in the mobility of chains.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Most of the recycling processes are based on the devulcanization of the material, which can mainly be achieved through physical and chemical processes. 3 Among the most used types of physical processes are: mechanical, 4,5 thermo-mechanical, [6][7][8][9][10][11] ultrasonic, [12][13][14][15][16] and microwave. [17][18][19][20][21] In the chemical process different organic amines, [22][23][24] disulfides, 25,26 mercaptans, 27 and inorganic systems [28][29][30] have been intensively studied.…”
Section: Introductionmentioning
confidence: 99%